Chilean Asian Studies on Art - Gonzalo Maire (Azijske študije (Spletna izd.), 2022)
The following article seeks to inquire further into the rules of formation upon which Asia—or that which is considered Asian—is represented in Art, and particularly, in Chilean museal collections. In this delimitation, the Museum is described as a regime of subjectivation of the experience of otherness. Starting from this working thesis and distancing the matter from the category of Asian Studies—if understood as a network of objectifying enunciations on Asia emerging from academia and the state—the museum’s regime is conceptualized as the place of production of a universal subject that is linked to otherness from the perspective of sameness. Our investigation argues that museum subjectification is defined by the experience of that which is real (objects) as both text and context: in other words, curatorial documents. At its core, the present article proposes an alternate manner in which to approach Asian objects—both material and cultural—from the second half of the nineteenth century outside of the Museum’s regime (and museal studies) in Chile, focusing the interest of study particularly on Asian Collecting.